PENGEMBANGAN LKS MATERI LISTRIK STATIS BERORIENTASI NILAI AL-QURâAN UNTUK SISWA KELAS IX SEKOLAH MUHAMMADIYAH - Cahyati, Friska; Suseno, Nyoto (Jurnal Pendidikan Fisika, 2015)
The objectives of this research and development was carried out to design a work-sheet of the static electricity material with Quran value and contant. Preliminary data is done in Muhammadiyah junior high schools of East Lampung.Â  Steps of Â research and development include, potential and problems analyst, gather information, design, validation, and revisions to the product. The instruments used to collect data by documentation, literature studies, questionaire and observation sheets. Aspect validity work-sheet include: didaktif, construction and Â techniques. The results showed that developed work-sheet was very good category. The advantages work-sheet improve not only knowledge but olso spiritual attitude. Disadvanteges was moment classroom activity the students more interested to the Al-Qurâan words then the material physics content.